Comprehensive Evaluation of Irradiance Transposition Models at High Temporal Resolution in Hot Desert Conditions - Abdul Wahab Ziaullah (23073781) (2025)
The tilted irradiance, or Plane-Of-Array (POA) irradiance, refers to the solar radiation that strikes a tilted surface, such as a photovoltaic (PV) panel. Accurate estimation of POA is essential for designing efficient solar systems and predicting energy output. POA can be calculated using transposition models that consider factors such as solar radiation components (direct and diffuse) and geometrical parameters like the tilt and azimuth angles. This study evaluates the performance of several widely used transposition models in the hot desert (BWh) climate of Doha, Qatar, using high-resolution (1-minute) irradiance data. A dataset spanning more than a year was analyzed with consideration of factors such as albedo, solar zenith angle, cloud cover, precipitation, and air quality. Several performance indicators, including relative RMSE, relative MBE, and a risk index, were utilized. Among the tested models, Perez and Perez-Driesse provided the closest agreement with POA irradiance at two south-facing tilt angles, showing stable performance across seasons, while Hay-Davies emerged as the least risky model. The analysis also revealed greater sensitivity to albedo at higher tilt angles. Model accuracy declined during cloudy and rainy periods, but improved during clear, dust-prone months. These findings highlight Qatar’s favorable atmospheric conditions for accurate POA modeling, supporting applications such as PV tilt optimization and system sizing, while underscoring the need for refined model tuning to address performance limitations under cloudy conditions. Other Information Published in: IEEE Access License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1109/access.2025.3617653